A Critical Role for the Presence of Lignocellulosic Material in the Determination of Wood Buffering Capacity. (2nd November 2017) - Król, Patryk; Toczyłowska-Mamińska, Renata; Mamiński, Mariusz
Abstract : The currently used determinations of wood buffering capacity, which are based on pH-metric titrations of aqueous wood extracts, neglect the effect of lignocellulosic material and the role of its insoluble constituents. This study examined the influence of the presence of wood in a system subjected to titration. A comparison of the results obtained from pine chip extracts and chip suspensions showed that the presence of wood and the wood-to-water ratio were critical factors that affected the measurement of the wood buffering capacity. The evidence showed that the resulting determination may vary by up to six times (0.28–1.99 ml/g), depending upon the conditions of the titration. In addition, it was found that the presence of wood had a neutralizing effect over the course of prolonged pH observations.